2019
DOI: 10.7759/cureus.3935
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Dermatomyositis: A Case Report and Review of Literature

Abstract: Juvenile dermatomyositis (JDM) is a systemic inflammatory disease involving children, which primarily affects the skin and the musculoskeletal system. The characteristic findings include Gottron papules, heliotrope rash, calcinosis cutis, and symmetric proximal muscle weakness. Histologically, it is characterized by the presence of lymphocytic vascular inflammation and endothelial swelling. Herein, we report a case of a 10-year-old girl of Indian origin, who presented to us with classical clinical and histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Juvenile dermatomyositis (JDM) is an inflammatory myopathy affecting striated muscle, skin, and the gastrointestinal tract with an incidence of 3.2 cases per million children ( 1 ). Patients experience proximal muscle weakness and exhibit characteristic skin findings including heliotrope rash, Gottron papules, calcinosis cutis, and periungual erythema & telangiectasias ( 2 ). Before the use of steroid therapy, JDM had a mortality rate of 40%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Juvenile dermatomyositis (JDM) is an inflammatory myopathy affecting striated muscle, skin, and the gastrointestinal tract with an incidence of 3.2 cases per million children ( 1 ). Patients experience proximal muscle weakness and exhibit characteristic skin findings including heliotrope rash, Gottron papules, calcinosis cutis, and periungual erythema & telangiectasias ( 2 ). Before the use of steroid therapy, JDM had a mortality rate of 40%.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of JDM is not well understood, but it has been hypothesized that it involves a combination of environmental triggers, immune dysfunction, and specific tissue responses ( 2 ) with contributions from both defective adaptive and innate immune responses. Approximately 65% of JDM patients have myositis-specific or myositis-associated antibodies ( 3 , 5 ), and B cell depletion with rituximab improves symptoms in some patients ( 6 , 7 ) implicating a potential role for B cells.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant ossification has also been observed in conditions treated with prostheses such as breast augmentation, [33] hip arthroplasty, [34] hyoid suspension, [35] temporomandibular joint reconstruction, [36] and tibiofibular syndesmosis, [37] and even in autoimmune diseases such as dermatomyositis, [38] systemic sclerosis, [39] and giant cell arteritis [40] . Foreign body giant cells have been observed in these autoimmune diseases, although not simultaneously with ossification [41–43] …”
Section: Discussionmentioning
confidence: 99%
“…[40] Foreign body giant cells have been observed in these autoimmune diseases, although not simultaneously with ossification. [41][42][43] Our comprehensive literature review revealed that aberrant ossification (metaplastic or heterotopic) occurred in various lesions or conditions with potential for foreign body reactions (Table 1). These findings suggest that aberrant ossification is closely related to foreign body reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Su propuesta en relación con la RSE se encuentra estrechamente ligada a este concepto y busca la legitimización del negocio por parte de la sociedad. Según esta teoría, la sostenibilidad y el éxito empresarial dependen no sólo del logro de metas económicas, sino de la satisfacción de las necesidades de los principales stakeholders de la organización (Pirsch;Gupta;Grau, 2007).…”
Section: Universidad Y Stakeholdersunclassified